The Priority Problems and Solutions in Formulating Strategies to Optimize Zakat Collection in Indonesia - Mochammad Ardani; Arif Pujiyono (International Journal of Zakat, 2022)
Zakat is giving part of the assets that are owned by a certain amount (nishab) at a certain time (haul) and giving it to a certain group (mustahik). The potential for zakat in Indonesia is very high, considering that the majority of Indonesia's population is Muslim. The potential for zakat collection in Indonesia is recorded at IDR 217 trillion, but zakat collection is still far from optimal. The amount of zakat funds that can be collected is only 10.22 trillion rupiah, which means 4.71% of the calculated potential. This research aims to determine priority problems, solutions, and formulating the strategies in optimizing zakat collection. The method used is the Analytical Network Process (ANP), which is a data analysis technique to formulate factor priorities and determine strategies based on several key informant perspectives with in-depth interview technique. This study took key informants from the Ministry of Religion, Badan Amil Zakat (BAZ), Lembaga Amil Zakat (LAZ), representatives of the Masyarakat Ekonomi Syariah (MES), and academics from MUI in achieving the research objectives. The results of the study explained that the priority problems in collecting zakat are low reporting, governance of zakat institutions, low of public awareness, and low of human resources. Priority solutions in collecting zakat are the provision of sharia audits, the establishment of SOPs for collecting zakat, zakat education, and establishing partners with social and humanitarian institutions. Strategies that can be implemented in optimizing zakat collection are tightening supervision for zakat institutions and increasing public’s trust toward amil zakat institutions.